Tutorial and Guidelines on Measurement of Sound Pressure Level in Voice and Speech - Švec, Jan G; Granqvist, Svante (Journal of speech, language, and hearing research, 2018)
Purpose: Sound pressure level (SPL) measurement of voice and speech is often considered a trivial matter, but the measured levels are often reported incorrectly or incompletely, making them difficult to compare among various studies. This article aims at explaining the fundamental principles behind these measurements and providing guidelines to improve their accuracy and reproducibility. Method: Basic information is put together from standards, technical, voice and speech literature, and practical experience of the authors and is explained for nontechnical readers. Results: Variation of SPL with distance, sound level meters and their accuracy, frequency and time weightings, and background noise topics are reviewed. Several calibration procedures for SPL measurements are described for stand-mounted and head-mounted microphones. Conclusions: SPL of voice and speech should be reported together with the mouth-to-microphone distance so that the levels can be related to vocal power. Sound level measurement settings (i.e., frequency weighting and time weighting/averaging) should always be specified. Classified sound level meters should be used to assure measurement accuracy. Head-mounted microphones placed at the proximity of the mouth improve signal-to-noise ratio and can be taken advantage of for voice SPL measurements when calibrated. Background noise levels should be reported besides the sound levels of voice and speech.
Keywords: Electrical Equipment and Supplies; Speech; tlak; hlas; Voice; směrnice pro lékařskou praxi jako téma; Speech Production Measurement; Practice Guidelines as Topic; měření tvorby řeči; elektrické vybavení a zdroje; Pressure; řeč